THE EFFECT OF GRANITE WASTE AS A FINE AGGREGATE SUBSTITUTION IN ASPHALT CONCRETE BINDER COURSE - NIKO FITRIANDANA RINJOKO; YONAS PRIMA ARGA RUMBYARSO; LYDIA DARMIYANTI (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2024)
Roads play a crucial role in local economies, supporting the distribution of goods and the mobility of citizens, but are often damaged by heavy traffic loads, poor drainage and inadequate infrastructure. Asphalt pavement is a popular choice due to its durability and affordable construction costs. Building waste includes construction and demolition waste, containing recyclable to toxic materials. Management of this waste is effective to reduce costs and support industry sustainability, in Indonesia, granite stone waste is widely generated. Analysis of Marshall characteristics in AC-WC mixtures using granite stone powder as a substitute for filler with a variation of 30% resulted in a stability value of 2487 kg, a VMA value of 36.51%, a flow value of 3.35 mm, a VIM value of 26.19% and an MQ value of 742 kg/mm that meets specifications. The VFB test value of 28.27% does not meet the 2018 Bina Marga specifications. While the granite stone powder with a variation of 60% produces a stability value of 2568 kg, a VMA value of 37.31%, a flow value of 3.4 mm, a VIM value of 27.12% and an MQ value of 756 kg/mm that meets the specifications. Meanwhile, the VFB test value of 27.31% does not meet the 2018 Bina Marga specifications. The presentation results of the mix design on cement filler are hot bin I by 17%, hot bin II by 45%, hot bin III by 32%, cement filler 6%, asphalt 6%.